2012
DOI: 10.1371/journal.pone.0032960
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Acupuncture Stimuli Using Brain Imaging with fMRI - A Systematic Review and Meta-Analysis of the Literature

Abstract: BackgroundThe mechanisms of action underlying acupuncture, including acupuncture point specificity, are not well understood. In the previous decade, an increasing number of studies have applied fMRI to investigate brain response to acupuncture stimulation. Our aim was to provide a systematic overview of acupuncture fMRI research considering the following aspects: 1) differences between verum and sham acupuncture, 2) differences due to various methods of acupuncture manipulation, 3) differences between patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(124 citation statements)
references
References 77 publications
6
116
0
2
Order By: Relevance
“…Neuroimaging studies investigating the acupuncture process have observed overlapping brain activations in the cortical sensorimotor and salient networks, as well as deactivations in the limbic-paralimbic neocortical network [7,13]. From a neurological point of view, the sensations induced by acupuncture are not only the product of the bottom-up modulation of simple needling at somatosensory receptors, but also of the reciprocal interaction of top-down modulation from the brain, such as the incorporation of focused attention and accentuated bodily awareness [21].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies investigating the acupuncture process have observed overlapping brain activations in the cortical sensorimotor and salient networks, as well as deactivations in the limbic-paralimbic neocortical network [7,13]. From a neurological point of view, the sensations induced by acupuncture are not only the product of the bottom-up modulation of simple needling at somatosensory receptors, but also of the reciprocal interaction of top-down modulation from the brain, such as the incorporation of focused attention and accentuated bodily awareness [21].…”
Section: Introductionmentioning
confidence: 99%
“…As described previously, acupuncture may cause the release of some mediators, which can inhibit substance P (a neurotransmitter that stimulates pain) and increase the release of cortisol, which helps the patients control their stress and anxiety (25). In addition, brain imaging studies have revealed that acupuncture varies the activation patterns in the pain processing areas of the brain (41). It is assumed that the needle stimulation causes the endogenous pain modulation's mechanisms to reduce pain perception; these mechanisms are diffuse noxious inhibitory controls, segmental inhibition, and descending pain control pathways (42,43).…”
Section: Discussionmentioning
confidence: 95%
“…19,20,22,24 Modern investigations into possible mechanisms of acupuncture have mixed results on the validity of meridians, but consistent across studies is involvement of the autonomic nervous system and hypothalamus-pituitary-adrenal (HPA) axis, recruited via peripheral sensory receptors. [37][38][39][40][41][42][43][44] Functional magnetic resonance imaging studies on humans found modulation of areas in the central nervous system involved in stress and nociception, such as the hypothalamus, nucleus accumbens, amygdala, hippocampus, and anterior cingulate gyrus. 39,[41][42][43][44] The downstream release of endogenous opioids is thought to contribute to subsequent analgesic and antipruritic effects.…”
Section: Discussionmentioning
confidence: 99%